O texto na apropriação da escrita - Giovani, Fabiana (Universidade Federal de São Carlos, 2006)
The main objective of this work is to understand the process of acquiring the writing system which children from the outskirts underwent during the literacy period. It was a peculiar situation in which the teacher, by using the enunciation theory as the foundation for her practice, became a researcher and constructed a corpus of analysis from the texts written by the children a material developed without aiming to be transformed into an academic research. The theoreticalmethodological presupposition of this qualitative investigation refers to a tracing paradigm of analysis which was established within the ambit of Human Sciences and enabled an analysis based on the traces present in the children s texts. The search for traces was related to the conditions or context in which the texts were produced, as well as to the set of stable characteristics of the discursive genre and the writing of the words. Consonant with these pillars which guided the sight to the texts is the choice for the theoretical referential mainly represented by Mikhail Bakhtin. From the traces in the texts, it was possible to comprehend that, in addition to the acquisition of the written language itself, there was a significant understanding of other relevant elements of language, such as the discursive genres which are present in our society, especially the written ones. Thus, in the end of the year, the children were shown to achieve autonomy when choosing a genre in an enunciation. Another trace which must be highlighted is the process by which the children manipulated a word and related it to the context in which they were involved. It was possible to observe that the words of others were dialogically reelaborated within my words of others through a process of utilizing different words of others , thus leading to the creation of my own words . In summary, this study provides evidence that carrying out a work aimed to guarantee the right to the written word for everyone is a viable way of establishing a dialog among unique and free subjects who understand, from the first contacts with writing, the meaning and the sense of the word equality .
Keywords: Lingüística; Alfabetização; Gêneros discursivos; Produção textual; CIENCIAS HUMANAS::EDUCACAO